Research on Application of Buckling Restrained Braces in Strengthening of Concrete Frame Structures - Ferdinand, Niyonyungu; Jianchang, Zhao; Qiangqiang, Yang; Wang, Guobing; Junjie, Xu (Civil Engineering Journal, 2020)
This paper examines the application of BRB in strengthening of reinforced concrete frame structures to meet seismic requirements according to Chinese seismic design code. Elastic response spectrum analysis and nonlinear time history analysis are performed by taking a real engineering example that suffers weak first floor irregularity due to added loads and addition of one floor. With the method of equivalent stiffness and displacement-based design method, buckling restrained brace parameters are deduced and are used to model BRB in ETABS using plastic wen model. Three configurations of buckling restrained braces are studied together with ordinary braces. Under elastic state, the relationship between the required cross section area of BRB and ordinary braces is deduced from the formula of calculating elastic bearing capacity where it is shown that the area of the ordinary braces must be 1.25 times that of BRB for ensuring the same performance. The results show that Inverted V brace configuration demonstrated better performance over single brace and V brace configurations and X brace configuration, although not recommended by Chinese code, is simulated and used in this paper and has demonstrated better performance over other configurations, and the further research on the practical use of this brace is recommended. Also, under action of strong earthquakes, by nonlinear time history analysis, buckling restrained braces demonstrated better performance of strengthening the structure and make it meet the requirement of code. Under this same condition, ordinary braces losses their bearing capacity due to excessive buckling.